Pondering Variables and Direct Instruction. - Hill, Robin K.; Guzdial, Mark (Communications of the ACM, 2019)
The article presents blog posts adapted from the website http://cacm.acm.org about the role of variables in computer programming and the direct instruction approach in computer programming education. The relations of variables to constants and values is addressed. Comments on the use of examples in computer programming instruction are presented.